Computer‐controlled liquid‐nitrogen drizzling device for removing frost from cryopreserved crystals. Issue 12 (4th December 2020) - Nakamura, Yuki; Baba, Seiki; Mizuno, Nobuhiro; Irie, Takaki; Ueno, Go; Hirata, Kunio; Ito, Sho; Hasegawa, Kazuya; Yamamoto, Masaki; Kumasaka, Takashi
Abstract : Cryocrystallography, which is commonly used in macromolecular crystallography, may sometimes reduce the quality of diffraction data and the visibility of crystals owing to frost adhesion. A device has been developed to remove frost by drizzling liquid nitrogen over the crystals, which enabled noise reduction of diffraction images and the centering of crystals with low visibility owing to frost adhesion. Abstract : Cryocrystallography is a technique that is used more often than room‐temperature data collection in macromolecular crystallography. One of its advantages is the significant reduction in radiation damage, which is especially useful in synchrotron experiments. Another advantage is that cryopreservation provides simple storage of crystals and easy transportation to a synchrotron. However, this technique sometimes results in the undesirable adhesion of frost to mounted crystals. The frost produces noisy diffraction images and reduces the optical visibility of crystals, which is crucial for aligning the crystal position with the incident X‐ray position. To resolve these issues, a computer‐controlled device has been developed that drizzles liquid nitrogen over a crystal to remove frost. It was confirmed that the device works properly, reduces noise from ice rings in diffraction images and enables the centering of crystals with low visibility owing to frost adhesion.